PENGARUH CASH RATIO, ROA, DER, PERTUMBUHAN PERUSAHAAN DAN INVESTMENT OPPORTUNITY SET TERHADAP DIVIDEND PAYOUT RATIO (Studi Pada Perusahaan Manufaktur Terdaftar di Bursa Efek Indonesia) - Lalu Rizal Ihwandi (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2019)
ABSTRACT The purpose of this study was to tested the effect of cash ratio (CR), return on assets (ROA), debt-to-equity ratio (DER), firm’s growth (Growth) and investment opportunity set (IOS) on dividend payout ratio (DPR) in manufacturing companies listed in the Indonesia Stock Exchange (IDX) for the period of 2008-2012. The population in this study were 214 manufacturing companies. Amount of samples were 28 companies with a five-year observation period. Amount of data were 140 observations by the method of pooled data. The sampling technique used was purposive sampling. The analysis technique used is multiple linear regression. The results of this study indicate that the cash ratio (CR), and debt-to-equity ratio (DER) significant positive effect on dividend payout ratio (DPR). While the return on assets (ROA) and the investment opportunity set (IOS) was not signifficant positive effect on the dividend payout ratio (DPR) as well as the firm’s growth (growth) significant negative effect on the dividend payout ratio (DPR). Determination kosefisien value by 17%. Keywords: cash ratio (CR), return on assets (ROA), debt-to-equity ratio (DER), firm’s growth (Growth), investment opportunity set (IOS) and dividend payout ratio (DPR)